A mixed-methods evaluation of unconscious racial bias training for NHS senior practitioners to improve the experiences of racially minoritised students. Issue 1 (20th January 2023) - Pennington, Charlotte R.; Bliss, Eleanore; Airey, Alisha; Bancroft, Mandy; Pryce-Miller, Maxine
Abstract : Objective: The degree awarding gap indicates that racially minoritised higher education students receive lower degree classifications relative to their white peers. While the reasons for this are complex, research suggests that educator and practitioner attitudes and behaviour towards racially minoritised students are a significant contributing factor. This preregistered study evaluates the effectiveness of unconscious racial bias training (URBT) to enhance National Health Service senior practitioner's recognition of how racial inequalities negatively impact racially minoritised students. Design: A mixed-methods study with a pretest and post-test design was conducted in the higher education and healthcare practice environment. Methods: Forty-nine NHS senior practitioners completed a 4-hour URBT workshop with activities focusing on activating stereotypes, exploring differences between unconscious and implicit bias, discussing the development of bias, and reflecting on student experiences of prejudice, harassment and discrimination. They completed pre- and post- quantitative measures that assessed the effectiveness of URBT and changes in racial competency, awareness and perceptions of unconscious racial bias. Qualitative measures explored the usefulness and perceived applications of URBT, and a 1-month follow-up assessed further how it had been applied within practice. Results: Participants reported positive evaluations of URBT, higher perceived racial competency, awareness and perceptions of racial bias (ps<0.001, dz>0.35). After 1 month, key themes from qualitative responses suggested that participants had increased self-awareness and were exploring how to set up mentoring and working groups, change recruitment and progression processes, and diversify the taught curriculum. Conclusions: URBT may be one effective strategy to enhance awareness and encourage reflections of racial bias. We discuss how reducing racial inequalities requires a multifaceted approach that affords upfront conversations about systemic racism, implements effective initiatives, policies and procedures, and engages in continuous evaluation.